A comprehensive study of the light soaking effect in ZnS/p-Si heterojunction solar cells. (1st September 2021) - Qiu, Kaifu; Xie, Qi; Meng, Lanxiang; Cai, Lun; Lin, Wenjie; Yao, Zhirong; Ai, Bin; Liang, Zongcun; Shen, Hui
Highlights: Light soaking effect is observed in ZnS/p-Si solar cells for the first time. Different light soaking conditions were systematically explored. A model is proposed to qualitatively explain the light soaking effect. Deep-level transient spectroscopy was applied to verify the proposed model. Abstract: An innovative dopant-free ZnS/p-Si heterojunction solar cell features hole selective WO3 contact were fabricated by thermal evaporation at room temperature. Light soaking effect was observed in the ZnS/p-Si heterojunction solar cells for the first time. The device performance is found to increase with the increasing light soaking times and finally reaches saturation. Besides, when the illumination stops, the power conversion efficiency (PCE) would decrease slightly. Device performance under different light soaking time and preservation time in the dark were investigated. Moreover, different monochromatic illuminations were conducted to further specify the active layer that is responsible for the light soaking effect. The result shows the ZnS layer and the short-wavelength light absorbed in ZnS layer are supposed to be the main reason for the effect. Based on these results, a model was proposed from the point of view of defect states variation in the energy band of ZnS to explain the effect. At last, Deep Level Transient Spectroscopy (DLTS) measurements with different monochromatic illumination were conducted to further verify the proposed model.